L-histidine-regulated zeolitic imidazolate framework modified electrochemical interface for enantioselective determination of L-glutamate. (20th December 2021) - Wei, Xiaofeng; Chen, Ying; He, Shan; Lian, Huiting; Cao, Xuegong; Liu, Bin
Abstract: Metal-organic framework (MOF)-based electrochemical interface presents a broad platform for the chiral recognition of amino acids, but the inferior conductivity of most MOFs limits the sensitivity in practical applications of electrochemical sensing. Therefore, the L-histidine-regulated zeolitic imidazolate framework (L-His-ZIF) was proposed as a novel electrochemical interface for simple, efficient, and enantioselective determination of L-glutamate (L-Glu) based on the electrochemical impedance spectroscopy (EIS). Based on the resistance change, the L-His-ZIF interface can be directly used for chiral recognition without the assistance of high-conductive substances, where multiple immobilizations are generally required in MOF-involved voltammetry. The stacked L-His-ZIF nano-polyhedrons provided numerous cavities and high specific surface area, thereby forming adequate chiral recognition sites. Based on the L-His-ZIF interface, the enantioselective detection of l -Glu-was successfully achieved with a good linear relationship with the impedance difference in the range from 0.1 nM to 50 nM with the detection limit of 0.06 nM. This prepared ZIF-functionalized electrode provided the desired enantioselectivity and reproducibility with robust chiral recognition in the real application. More importantly, MOF-modified EIS can be applied for more chiral recognition of enantiomers by various MOF interfaces, which has great potential for applications in pharmaceutical monitoring and biochemical analysis.